EXPLORING COMMUNITY PARTICIPATION AT ECOTOURISM SITES IN THE UPPER EAST REGION, GHANA - Boatbil, C. S.; Yorose, W. A.; Yiran, A. B. (UDS International Journal of Development, 2025)
This paper explores the extent of community participation at four selected ecotourism sites focusing on local control, personal benefits, community-based benefits, and personal involvement. A mixed method approach was adopted. Results revealed locals participated with little personal benefits(i.e personal incomes, employment, consultations, meeting attendance, policy formulation and decision-making). Tourism development was locally controlled yet a few tourism committee members and tour guides carried out its activities except at Gunwoku in Sirigu. The study recommends information sharing with all community members and tourism authorities. Government must improve existing infrastructure as well as the skills and financial capabilities of local residents. Keywords: Community, Ecotourism, Participation, Tourism, Sustainability